The Impact of Economic Policies on Poverty and Income Distribution : Evaluation Techniques and Tools - Bourguignon, Francois; Pereira da Silva, Luiz A. (Washington, DC: World Bank and Oxford University Press, 2013)
Development is about fundamental change in economic structures, about the movement of resources out of agriculture to services and industry, about migration to cities and international movement of labor, and about transformation in trade and technology. Social inclusion and change-change in health and life expectancy, in education and literacy, in population size and structure, and in gender relations-are at the heart of the story. The policy challenge is to help release and guide these forces of change and inclusion. But how can policymakers assess whether what they have done, or what they are doing, is right? Since the 1970s public economics has placed the serious analysis of growth at the center of its agenda. It has shown how to integrate growth and distribution - in simple terms, the size of the cake, and the distribution of the cake-rigorously into the discussion of public policy, both theoretically and empirically.